Applied Fracture Mechanics - Belov, Alexander (IntechOpen, 2012)
The book "Applied Fracture Mechanics" presents a collection of articles on application of fracture mechanics methods to materials science, medicine, and engineering. In thirteen chapters, a wide range of topics is discussed, including strength of biological tissues, safety of nuclear reactor components, fatigue effects in pipelines, environmental effects on fracture among others. In addition, the book presents mathematical and computational methods underlying the fracture mechanics applications, and also developments in statistical modeling of fatigue. The work presented in this book will be useful, effective, and beneficial to mechanical engineers, civil engineers, and material scientists from industry, research, and education.